Influence of Fe substitution on the Jahn–Teller distortion and orbital anisotropy in orthorhombic Y(Mn1−xFex)O3 epitaxial films. Issue 31 (18th July 2016) - Haw, Shu-Chih; Lee, Jenn-Min; Chen, Shin-Ann; Lu, Kueih-Tzu; Lee, Ming-Tao; Pi, Tun-Wen; Lee, Chih-Hao; Hu, Zhiwei; Chen, Jin-Ming
Abstract : The variation of the Jahn–Teller distortion and orbital anisotropy in orthorhombic YMnO3 single-crystal film upon Fe substitution was reported. Abstract : Multiferroic YMn1− x Fe x O3 (020) ( x = 0.125, 0.25, 0.50) epitaxial thin films with an orthorhombic structure (space group Pbnm ) were prepared on a YAlO3 (010) substrate by pulsed-laser deposition. Upon Fe substitution, the b -axis was clearly shortened, whereas the a - and c -axes were slightly lengthened based on XRD analysis. To understand the influence of orbital polarization and the Jahn–Teller effect of Mn 3+ on Fe substitution and also the local octahedral-site distortion of Fe 3+ in an environment of Jahn–Teller-active Mn 3+ ions in YMn1− x Fe x O3 films, we measured the polarization-dependent X-ray absorption spectra at the Mn-L2, 3 and Fe-L2, 3 edges, and also simulated the experimental spectra using configuration-interaction multiplet calculations. Although Δeg for the Mn 3+ ion decreased from 0.9 eV in pure YMnO3 to 0.6 eV in the half-Fe-substituted sample, a single eg electron was still strongly constrained to the d3 y 2 − r 2 orbital for all the Fe concentrations tested. The largest Δeg, 0.5 eV, for the Fe 3+ ion was derived for a sample with 12.5% Fe substitution, and gradually decreased to 0.15 eV for the half-Fe-substituted sample. The local octahedral-site distortion of the Fe 3+ ion inside the YMnO3 lattice was similar to that of the Mn 3+ ion, whereas the Jahn–Teller distortion and GdFeO3 -type distortion of the Mn 3+ ion were decreased by the spherical high-spin Fe 3+ ions. The combination of the experimental and theoretical data provides both profound insight into the variation of the Jahn–Teller distortion and orbital anisotropy and instructive information about the magnetic structures in these orthorhombic YMn1− x Fe x O3 thin films.